2016
DOI: 10.1093/pcp/pcw200
|View full text |Cite
|
Sign up to set email alerts
|

ThaleMine: A Warehouse for Arabidopsis Data Integration and Discovery

Abstract: ThaleMine (https://apps.araport.org/thalemine/) is a comprehensive data warehouse that integrates a wide array of genomic information of the model plant Arabidopsis thaliana. The data collection currently includes the latest structural and functional annotation from the Araport11 update, the Col-0 genome sequence, RNA-seq and array expression, co-expression, protein interactions, homologs, pathways, publications, alleles, germplasm and phenotypes. The data are collected from a wide variety of public resources.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…To test whether the genes we have uncovered are expressed, and whether they have expression levels similar to validated gene models, we condensed the expression profile of all rice and A. thaliana genes from diverse RNA‐sequencing datasets into density plots of their maximum expression (purple distributions in Fig. ; Table S4) (Kawahara et al , ; Krishnakumar et al , ). As in maize (Walley et al , ), we observed bimodal expression distributions for both A. thaliana and rice genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether the genes we have uncovered are expressed, and whether they have expression levels similar to validated gene models, we condensed the expression profile of all rice and A. thaliana genes from diverse RNA‐sequencing datasets into density plots of their maximum expression (purple distributions in Fig. ; Table S4) (Kawahara et al , ; Krishnakumar et al , ). As in maize (Walley et al , ), we observed bimodal expression distributions for both A. thaliana and rice genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression profiles were collected for poplar from P op G en IE (Sundell et al , ), for tomato from the Tomato Expression Atlas (Fernandez‐Pozo et al , ), for A. thaliana from Thalemine (Krishnakumar et al , ), for maize from qTeller (Schnable, ), and for rice from the Rice Annotation Project (Kawahara et al , ). Correlation of gene pair expression was analyzed using Pearson's product‐moment correlation (Table S4; Best & Roberts, ).…”
Section: Methodsmentioning
confidence: 99%
“…Tables of DEGs for each comparison were combined and analyzed through Microsoft Excel, in order to generate lists of Arabidopsis Genome Initiative (AGI) identifiers with their corresponding [Log 2 (Fold Change)] values. Machine annotation of AGI ID lists was carried out using G:Profiler (Raudvere et al, 2019), while the TAIR (Lamesch et al, 2011;Berardini et al, 2015) and Araport ThaleMine (Krishnakumar et al, 2016) databases were used to investigate genes of interest. DEGs of a comparison (e.g., FLT vs. GC) with a greater than twofold change in at least one context of the comparison were retained for analysis (Supplementary File S1).…”
Section: Rna-seq Data Analysismentioning
confidence: 99%
“…Cell type-specific localization might also result from alternative mRNA splicing generating multiple protein isoforms. However, the current A. thaliana genome annotation (Krishnakumar et al 2017) only predicts a single FH1 mRNA comprising four exons. Also all empirically obtained cDNA sequences derived from the At3g25500 locus found in the GenBank database match the predicted splicing pattern, or at least are consistent with it (Supplementary data Figure S11).…”
Section: Discussionmentioning
confidence: 99%